TPM4 condensates glycolytic enzymes and facilitates actin reorganization under hyperosmotic stress - Wenzhong Yang; Yuan Wang; Geyao Liu; Yan Wang; Congying Wu (Cell Discovery)
Abstract Actin homeostasis is fundamental for cell structure and consumes a large portion of cellular ATP. It has been documented in the literature that certain glycolytic enzymes can interact with actin, indicating an intricate interplay between the cytoskeleton and cellular metabolism. Here we report that hyperosmotic stress triggers actin severing and subsequent phase separation of the actin-binding protein tropomyosin 4 (TPM4). TPM4 condensates recruit glycolytic enzymes such as HK2, PFKM, and PKM2, while wetting actin filaments. Notably, the condensates of TPM4 and glycolytic enzymes are enriched of NADH and ATP, suggestive of their functional importance in cell metabolism. At cellular level, actin filament assembly is enhanced upon hyperosmotic stress and TPM4 condensation, while depletion of TPM4 impairs osmolarity-induced actin reorganization. At tissue level, colocalized condensates of TPM4 and glycolytic enzymes are observed in renal tissues subjected to hyperosmotic stress. Together, our findings suggest that stress-induced actin perturbation may act on TPM4 to organize glycolytic hubs that tether energy production to cytoskeletal reorganization.